COVID-19: asymptomatic carrier transmission is an underestimated problem. (2020) - Zhao, Hongjun; Lu, Xiaoxiao; Deng, Yibin; Tang, Yujin; Lu, Jiachun
Abstract: At the present time, COVID-19 is spreading rapidly [1 ]. The global prevention and control of COVID-19 is focused on the estimation of the relevant incubation period, basic reproduction number ( R 0 ), effective reproduction number ( R t ) and death risk. Although the prevention and control of COVID-19 requires a reliable estimation of the relevant incubation period, R 0, R t and death risk. Another key epidemiological parameter-asymptomatic ratio that provides strength and range for social alienation strategies of COVID-19, which is widely defined as the proportion of asymptomatic infections among all disease infections. In fact, the ratio of asymptomatic infection is a useful indicator of the burden of disease and a better measurement of the transmissibility of the virus. So far, people have not paid enough attention to asymptomatic carriers. The asymptomatic carriers discussed in this study are recessive infections, that is, those who have never shown symptoms after onset of infection. We will discuss three aspects: detection, infectivity and proportion of healthy carriers.